Nutritional considerations for postoperative recovery in orthopaedic surgeries - Sahoo, Priyank; Pal, Ananda Kisor; Agarwal, Neha; Sadhukhan, Priyanka; Bhoite, Rachana (International Journal of Research in Orthopaedics, 2025)
India has witnessed a substantial increase in joint replacement surgeries over the past two decades. Despite surgical advances, suboptimal nutritional status remains a major determinant of poor postoperative outcomes, including delayed wound healing, muscle atrophy, and increased infection risk. Protein energy malnutrition (PEM) is a strong predictor of adverse outcomes and delayed wound healing. Supplementation with high quality protein, essential amino acids (EAAs), and β-hydroxy β-methylbutyrate (HMB) have demonstrated benefits in preserving muscle mass, promoting anabolic recovery and reducing postoperative complications. Emerging evidence suggests promising roles for collagen, hyaluronic acid, and plant-based nutraceuticals in orthopaedic recovery, though the extent of impact of these nutrients remain underexplored. Collagen peptides may enhance wound healing, connective tissue regeneration, and mitigate the relapse of osteoarthritis (OA). Hyaluronic acid, with its immunomodulatory and regenerative functions, shows potential in post-surgical tissue repair and symptom relief. Furthermore, plant-derived bioactives such as curcumin, Boswellia serrata, and palmitoylethanolamide (PEA) demonstrate anti-inflammatory and analgesic effects, offering alternatives to conventional NSAIDs with fewer adverse effects. This review evaluates the current evidence supporting perioperative nutritional strategies to enhance recovery following orthopaedic surgeries.